Critical Limb Ischemia In a Diabetes Mellitus Patient with Atrial Fibrilation - Caesar Lagaliggo Givani; Hermina Novida (Universitas Airlangga, 2020)
Critical Limb Ischemia (CLI) is a clinical syndrome in the form of ischemic pain, especially at rest or a tissue loss condition, such as an ulcer or gangrene that does not heal, associated with Peripheral Arterial Disease (PAD). Diabetes mellitus (DM) accelerates atherosclerosis and becomes one of the risks of PAD. It is also known to accelerate the worsening of PAD with a 4x greater risk of developing CLI compared to patients without DM. At the other side, 60-95% of patients who are operated on as a result of limb ischemia are diagnosed with atrial fibrillation (AF). This paper is a case report regarding a patient with CLI as a complication of DM and AF.